Secondary sources about calendar aspect of baptism and name choice in Medieval Rus’ - Lyudmila Goryushkina (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article "Secondary sources about calendar aspect of baptism and name choice in Medieval Rus’" is devoted to the researches of the 19th - the beginning of the 21th centuries that cover the issue of the main customs of early days of babies’ lives connected with calendar such as the name choice and baptizing. Firstly this studying was begun in the works devoted to the history of daily life, Orthodox church and Liturgics. The questions were raised as if a child might have several calendar names and how they were chosen, how its birthday was connected with the name-day and the day of baptizing. The range of sources was formed and two ways for research were settled: studying of orders how name and baptism day should be chosen and studying of the real practice. After the Revolution the research was cancelled. Its revival happened in the second half of the 20th century in papers on philology and history. There were no new topics, but deeper investigation of settled ones. The investigation of these questions differs: choice of name is considered deeper than baptism. Most of the scholars suppose day of birth and name-day to be close and calendar to be an important factor of name choice. The idea was put forward to a widespread custom of two calendar names, official and secret, one of which strictly depended on calendar. Baptism is generally supposed to be performed on the 40th day, but it was not so obligatory. Generally there was no aim of studying connection between all three days. Further research is welcomed, cause some aspects are still disputable. Comprehensive study of all calendar aspects of name choice and baptism is needed and more consistent division of desirable order and real practice as well. Lastly, deeper investigation of found source types is desirable.